The State Obligation to Provide Emergency Contraception for Rape Survivors: A Human Rights Perspective in Indonesia - Iqbal Kamalludin; Ani Purwanti; R. B. Sularto; Vasyl Berezniak; Valentyn Liudvik; Bhanu Prakash Nunna (Sawwa: Jurnal Studi Gender, 2026)
Sexual violence is a serious human rights and public health issue because rape survivors face a high risk of unwanted pregnancy. Emergency contraception (EC) is recognized internationally as an essential health service that states are obliged to prov ide. This study examines Indonesia’s compliance with international human rights obligations regarding EC access for rape survivors and identifies gaps in the national legal framework. Using a normative legal approach, the research analyzes Indonesian regulations alongside international human rights standards. The findings show a gap between legal commitments and practical implementation. Although Indonesian laws recognize survivors’ healthcare rights, EC is not explicitly mandated, leading to inconsistent access, stigma, bureaucratic barriers, limited facilities, and inadequate gender-sensitive training for healthcare workers. EC access is therefore a fundamental human rights obligation requiring stronger legal protections.